The Effect of Pressing Fish Waste Meal at Pasar II Natal on Protein, Fat, and Energy Content - Warisman; Dini Julia Sari Siregar (The International Conference on Education, Social Sciences and Technology (ICESST), 2023)
The purpose of this study was to determine the effect of pressing fish waste flour in the Christmas II market on protein, fat, and energy content. The research method used in this study was a completely randomized design (CRD), which consisted of 4 treatments and 5 replications. The following were performed: P0: Fish waste flour from poultry; P1: Fish waste flour is dried under the sun; P2: Fish waste flour is pressed and dried in the sun; P3: Fish waste flour is pressed in the oven with a temperature of 400C. The research parameters are the content of crude protein, crude fat, and gross energy. The results of this study showed that the effect of pressing fish waste flour on the II Natal market showed that the highest crude protein content was in the P0 treatment (fish waste flour from poultry); Crude fat and gross energy were highest in treatment P1 (fish waste flour dried under the sun). The results of analysis of crude protein in samples of fish meal treatment, it was found that the one with the highest crude protein content was treatment P0 (fish waste flour from poultry) which was 53.07% then treatment P2 (pressed fish waste flour dried under the sun) with an average 43.31% and P3 (pressed fish waste flour in the oven with a temperature of 400C) of 42.66% and the one with the lowest crude protein content was 41.81%, namely treatment P1 (waste fish flour dried under the sun). The lowest percentage of crude fat content was found in treatment P0 (fish waste flour from poultry) which was 0.16% and the highest was in treatment P1 (dried fish waste flour in the sun) which was 2.93% and the highest gross energy was 2,852.46 cal /100g in treatment P1 (fish waste flour drying under the sun), and the lowest was 2,252.63 cal/100g in treatment P0 (fish waste flour from poultry). The results of the analysis of variance for the content of crude protein, crude fat, and gross energy content showed very significant differences (P<0.01) in this study. The results of the test of variance which were very significantly different were then tested further using the honest significant difference (BNJ) follow-up test according to the respective coefficient of diversity.